Pro Kontra Fatwa Dana Talangan Haji: - Hakim, Rahmad (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2018)
This paper aims to conduct an in-depth analysis of the positive and negative impact of the hajj financing funds that have been set out in the fatwa of DSN-MUI from the perspective of maslahah mursalah. Although it has long been established and has been implemented, but the debate surrounding the legalization of hajj bailout funds is still occur among the people. Some people feel the benefits of this fatwa, while some people question its validity; especially in terms of ability (istita?ah) of performer of the Hajj using this facility. In addition, this is also considered to be able to extend the hajj queue. The question that should be answered is what is the problem and the benefits of this hajj financing, if viewed from the perspective of maslahah mursalah. This study uses a type of qualitative-descriptive research with diverse collection methods; documentary and interview. The conclusion of this study is that the hajj financing still benefits to the ummah.